Contrast‐Enhanced Ultrasound in Pulmonary Lymphoma: A Small Pilot Study. (6th May 2018) - Trenker, Corinna; Wilhelm, Christian; Neesse, Albrecht; Rexin, Peter; Görg, Christian
Abstract : Here, we describe the appearance and pattern of pulmonary lymphoma on B‐mode imaging and with contrast‐enhanced ultrasound (CEUS). From July 2009 to December 2015, 6 patients with histologically or cytologically confirmed lymphoma of the lung were examined by B‐mode imaging, followed by CEUS. A retrospective analysis of the imaging data was performed with respect to the time to enhancement, pulmonary artery (PA) and bronchial artery, echogenicity (hypoechoic, isoechoic, or hyperechoic), and homogeneity (homogeneous or inhomogeneous) of the contrast enhancement. On B‐mode imaging, all 6 pulmonary lymphoma lesions were hypoechoic. Five cases had PA enhancement, and 1 case had bronchial artery enhancement on CEUS imaging. Strikingly, all 6 patients had isoechoic arterial contrast enhancement. In the parenchymal phase, 3 of the lymphoma lesions showed hypoechoic contrast enhancement, and 3 showed isoechoic enhancement. Pulmonary lymphomas are hypoechoic on B‐mode imaging. With CEUS, all patients had predominant PA contrast enhancement in the arterial phase with variable parenchymal contrast enhancement. Thus, definite differentiation from other malignant or benign pulmonary lesions cannot be achieved by CEUS.